Emerging role of miRNAs in the regulation of ferroptosis - Mahmoudi-Lamouki, Reza; Kadkhoda, Sepideh; Hussen, Bashdar Mahmud; Ghafouri-Fard, Soudeh (Frontiers in Molecular Biosciences, 2023)
Ferroptosis is a kind of cell death which has distinctive features differentiating it from autophagy, necrosis and apoptosis. This iron-dependent form of cell death is described by an increase in lipid reactive oxygen species, shrinkage of mitochondria and decrease in mitochondrial cristae. Ferroptosis is involved in the initiation and progression of many diseases and is regarded as a hotspot of investigations on treatment of disorders. Recent studies have shown that microRNAs partake in the regulation of ferroptosis. The impact of microRNAs on this process has been verified in different cancers as well as intervertebral disc degeneration, acute myocardial infarction, vascular disease, intracerebral hemorrhage, preeclampsia, hemorrhagic stroke, atrial fibrillation, pulmonary fibrosis and atherosclerosis. miR-675, miR-93, miR-27a, miR-34a and miR-141 have been shown to affect iron metabolism, antioxidant metabolism and lipid metabolism, thus influencing all pivotal mechanisms in the ferroptosis process. In the current review, we summarize the role of microRNAs in ferroptosis and their involvement in the pathetiology of malignant and non-malignant disorders.